Sugar and salt : a novel - Wiggs, Susan (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2022)
"Jerome Sugar learned the art of baking in his grandma's bakery, also called Sugar, on historic Perdita Street in San Francisco. He supplies baked goods to the Lost and Found Bookshop across the street. When the restaurant that shares his commercial kitchen loses its longtime tenant, a newcomer moves in: Margot Salton, a barbecue master from Texas. Margot isn't exactly on the run, but she needs a fresh start. She's taken care of herself her whole life, pulling herself up by her fingernails to recover from trauma, and her dream has been to open a restaurant somewhere far, far from Texas. The shared kitchen with Jerome's Sugar bakery is the perfect setup: a state-of-the-art kitchen and a vibrant neighborhood popular with tourists and locals. Margot instantly takes to Jerome's mother, the lively, opinionated Ida. The older woman proves to be a good mentor, and Margot is drawn to Jerome. Despite their different backgrounds their attraction is powerful--even though Jerome worries that Margot will simply move on from him once she's found some peace and stability. But just as she starts to relax into a happy new future, Margot's past in Texas comes back to haunt her." -- Book jacket.
Includes recipes.
Keywords: Bakers -- Fiction; Cooks -- Fiction; Man-woman relationships -- Fiction; Friendship -- Fiction; Romance fiction; Domestic fiction